Effect of oxidation on the bending fatigue behavior of an advanced SiC/SiC CMC component at 1000 °C in air. Issue 10 (August 2022) - Patel, Amit; Sato, Eiichi; Takagi, Takeshi; Shichijo, Naohiro
Abstract: The present study elucidates the effect of oxidation during static and fatigue loading in SiC/SiC CMC structured component, which shows damage in the stress-concentrated region. It is made of Tyranno SA3 fiber, BN (Boron nitride) interphase, and CVI (chemical vapor infiltration) + PIP (polymer impregnation and pyrolysis) hybrid matrix. The comparison based on strength and fracture morphology was made. After annealing, the as-received sample showed minute oxidation and slightly enhanced strength. The fatigued sample without annealing under low stress showed higher retained strength than the as-received sample due to smooth debonding. The fatigued sample with annealing under high stress showed a loss in strength than the as-received sample owing to the formation of a significant amount of borosilicates glasses, which further promoted SiO2 formation between fiber and matrix and caused the brittle failure. However, simultaneous filling borosilicate glasses into the pores oppositely aided in maintaining the retained strength. Graphical Abstract: ga1 Highlights: The effect of oxidation in the SiC/SiC CMC during bending fatigue was studied. Maximum retained strength was achieved after low-stress fatigue. Oxidation due to annealing via matrix-cracking led to severe strength degradation at high-stress fatigue. The filling borosilicate glasses into the fiber-tow pores aids in keeping the high retained strength.